The Principle of Composite Sentencing: Its Centrality to, and Implications For, the ASBO - Stuart Macdonald (Criminal Law Review, 2006)
One of the primary objectives of the ASBO was to provide a mechanism for the imposition of "composite sentences" on those who persistently commit serious anti-social behaviour which repeatedly affects the same victims. It is this that was used to justify the severe maximum sentence for breach of an ASBO. Yet the courts have denied the relevance of the principle of composite sentencing. This has resulted in confusion, not only over the penalties which should be applied to individuals found to have breached their ASBO, but also over the role of the order itself. This article accordingly argues that composite sentencing should be recognised as an integral feature of the ASBO’s design, and outlines three implications which would follow for the ASBO.